PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH (ICM) DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 24 PADANG TAHUN PELAJARAN 2012/2013 - Fitri, Nova Anggelia; Nasution, Minora Longgom; Cesaria, Anna (STKIP PGRI Sumbar, 2013)
This research is motivated by the difficulty students answer the teachers questions about previous material and students comprehension of mathematical concepts are still low. This study aimed to determine whether the learning outcomes of students comprehension of mathematical concepts are applied to the type of active learning strategies Index Card Match (ICM) accompanied Handout better than the learning outcomes of students who applied to conventional teaching. This type of research is experimental research, the research design Against Random Subjects. The data analysis technique used is the one party t test with the help of MINITAB software. Hypothesis test results obtained p-value equal to 0.041 means less than Î± = 0.05, then the hypothesis in this study received thus concluded that the learning outcomes of students comprehension of mathematical concepts are applied to the type of active learning strategies Index Card Match (ICM) with more Handout better learning outcomes than students who applied to conventional teaching in class VIII SMP 24 Padang.